COMPETENCY BASED TRAINING KEWIRAUSAHAAN PENINGKATAN MENTAL WIRAUSAHA MAHASISWA - Suranto Suranto (Kaunia: Integration and Interconnection Islam and Science, 2012)
The purpose of this study was to determine whether the model of competency based training in entrepreneurial skills to improve the ability of prospective graduate business education courses to students of Chemistry and Chemical Education, Faculty of Science & Technology, Islamic State University (UIN) Sunan Kalijaga The data were obtanined from 50 students of The Study Program of Chemistry and Chemical Education. The collection of data was by questionnaire, observation, and interviews. The data analysisused regression analysis to determine the effect of variable competency based training (X) of variable mental effort (Y). Known results of the regression equation Y = 17 591 + 1.080X. This equation means that the better model of competency based training in entrepreneurship given the better mental effort learners possessed. The magnitude of the influence model of competency based training to the mental operations of 0886 or 88.6%. Thus the provision of competency based training materials in the field of mental effort can influence the entrepreneurial potential of graduates of chemistry and chemical education.